Inkubator Telur Ayam Menggunakan Lampu DC Dengan Kontrol PID - Hendriawan, Ade (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Abstract - Hatching of chicken eggs or incubators is a tool to petrify the hatching process by using incandescent lamps as a substitute for the hatching process of hens, In the industry Chicken poultry hatchery cultivation is very important in terms of temperature stability especially using artificial incubators. The incubator circulating on the market today only uses the reley system, which works on and off on a very long time to reach the steady state. The purpose of this research is to make chicken egg slot deposit 5000 incubatot using dc lamp and lm35 sensor with Proportional Integral Derivative (PID) control. In this experiment we can find out the values of Proportional gain (Kp), Integral Time (Ti), and Derivative Time (Td). Keyword : PID, lm35 sensor, DC light, Chicken Egg Incubator